Basic points of the Antropic Attitude Theory - Nadirashvili, D.; S., † Nadirashvili (Psichologija, 2013)
The reason for the introduction of the concept of attitude was the explanation of illusory perceptions. On the basis of experimental studies D. Uznadze demonstrated that the illusions of perception are connected not solely to the motor activity sphere. It can appear in every modality of perception. J. Piaget called the phenomenon identified in the above-mentioned method “the Uznadze effect” and used it for the characterization of specific stages of the development of intellect. Social attitude, in addition to the unprejudiced objective reality, implies disposition towards other people, social environment. Attitudes, besides differing by the content and components that are depicted in them, differ from each other by ways of formation. Characterization of social attitudes is performed according to what disposition exists towards the social values expressed through them. Its peculiarities are measured on a number scale. For this purpose we use an 11-point scale. On this scale, attitude is characterized by: valency – positive-negative disposition for social values; valency intensity – how more intensive is attitude valency according to positivity and negativity; the zone of acceptance, which expresses the intensity of attitudes acceptable for a person; the zone of toleration – a zone of the intensity of attitudes, which can be tolerated by a person; sharpness-diffusivity attitude, which shows by how many steps can the attitude of a person be characterized, etc. On the human being level of psyche development, conscious, cognitive, and moral behaviors emerge. Attitudes are actively involved in these processes as well. At the highest level of psyche development, the activity of a human being is determined by social attitudes.